Reflexive Conversations: Constructing Hermeneutic Designs for Qualitative Management Research. (11th June 2015) - Robinson, Sarah; Kerr, Ron
<x xml:space="preserve">Abstract</x> Responding to calls to widen the range of qualitative approaches within management research, this paper addresses perceived difficulties in applying hermeneutic approaches to interview‐based research and discusses how researchers can develop appropriate research designs. It reviews how tools from the hermeneutic tradition have been used, demonstrating how a sub‐branch, critical hermeneutics, is particularly suited to the complexities of management research, offering a flexible means of exploring complex research relationships between 'texts', contexts and the researcher. The paper details the inception and implementation of a hermeneutic research project and demonstrates the application of a four‐stage hermeneutic analytical framework for use with interview transcripts. In showing how interviews are co‐created through a hermeneutic process between the research participants and the researcher, the paper suggests ways of acknowledging the implications of this relationship and thus of increasing researcher reflexivity within the research process. The benefits and limitations of implementing such hermeneutic research designs are then discussed.